Nonlinear Dynamics Analysis of a Continuum Rotor through Generalized Harmonic Balance Method - Luo, Haiyang; Wang, Yuefang (Journal of Applied Nonlinear Dynamics, 2026)
The dynamics of a continuum rotor system excited by nonlinear oilfilm force and electromagnetic force is investigated through the Generalized Harmonic Balance Method. The governing differential equation of the continuum rotor system is reduced through the Galerkin’s approximation method. Firstly, the motion in Y-direction is considered as the response of a planar continuum rotor. The analytical periodic motion is obtained and the bifurcation and stability is determined. Secondly, the dynamical model of a spatial continuum rotor is studied. The stability and bifurcation of the analytical periodic motion is obtained and compared to numerical results to show the accuracy of the Generalized Harmonic Balance Method.